Metacarpal sign - Nieradko-Iwanicka, Barbara (Journal of Education, Health and Sport, 2018)
Background Archibald's sign, or metacarpal sign is defined as shortening of the IV and V metacarpal bones, is a rare phenomenon found in the Turner syndrome, homocystinuria and in Albright's osteodystrophy. Objectives The aim of the article was to show a rare case of metacarpal sign with atypical shortening of the III and IV metacarpal bones not connected with gonadal dysgenesia, genetic disorders nor osteodystrophy. Material and methods Case report of a 60-year-old female patient. Results Artchibald's metacarpal sign in the described case was accompanied by erosive arthritis in the left lower extremity. No features of genetic disorders nor gonadal disgenesia were found in the patient. Undifferentiated seronegative asymmetric erosive arthritis developed in the patient. The level of parathormon was within the normal range. No signs of tumor were seen in bone scintigraphy. Conclusions Archibald's metacarpal sign may be present in patients without genetic disorders.